2018
DOI: 10.3390/cancers10110397
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Predicts the Response of Triple-Negative Breast Cancers to All-Trans Retinoic Acid

Abstract: All-trans retinoic acid (atRA) regulates gene expression and is used to treat acute promyelocytic leukemia. Attempts to use atRA in breast cancer without a stratification strategy have resulted in limited overall effectiveness. To identify biomarkers for the treatment of triple-negative breast cancer (TNBC) with atRA, we characterized the effects of atRA on the tumor growth of 13 TNBC cell lines. This resulted in a range of effects that was not predictable based on previously hypothesized predictors of respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Error bars represent standard deviation (n.d. = not detected) associated with poor prognosis, actively promotes tumor growth, invasion, and metastasis, contributes to chemoresistance in multiple cancers, and has been proposed as a therapeutic target [23, 25, 27-31, 36, 61-70]. ALDH1A3's tumor-promoting activities are in part mediated by its generation of retinoic acid and subsequent gene expression changes; [27,71] however, it is unclear which are ALD-H1A3's key downstream oncogenic effectors. Identifying these effectors would delineate the mechanism of ALDH1A3 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent standard deviation (n.d. = not detected) associated with poor prognosis, actively promotes tumor growth, invasion, and metastasis, contributes to chemoresistance in multiple cancers, and has been proposed as a therapeutic target [23, 25, 27-31, 36, 61-70]. ALDH1A3's tumor-promoting activities are in part mediated by its generation of retinoic acid and subsequent gene expression changes; [27,71] however, it is unclear which are ALD-H1A3's key downstream oncogenic effectors. Identifying these effectors would delineate the mechanism of ALDH1A3 in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that KLF2 suppresses the expression of FABP5 in MCF-7 cell line [78]. However, a recent paper found conflicting result related to FABP5/CRABPII ratio implication on ATRA sensitivity in triple-negative breast cancer [79], so that further data are needed, especially for other solid cancer types than breast.…”
Section: Cytoplasmic Trafficking Defective Rbps Expressionmentioning
confidence: 99%
“…Following the studies that highlighted the retinoic acids' activity in suppressing the growth of different cancer cell lines, some studies focused on the genes expressed after the retinoid acids' treatment as probably tumor suppressor genes. A recent paper of Coyle and colleagues found that between 13 triple-negative breast cancer cell lines, 1400 sites were differentially methylated between ATRA resistant and sensitive cell lines [79]. Considering that the retinoic acids can activate the transcription factors that exert their action by biding to the RARE present on the promoter of the retinoid-responsive genes, impaired transcription on these genes might determine the retinoid acids' resistance.…”
Section: Retinoid-responsive Genesmentioning
confidence: 99%
“…A large mass of pre-clinical data indicates that ATRA is a promising agent in the prevention/treatment of breast cancer [5][6][7]. Breast cancer (BC) is a very heterogeneous disease [8] which is traditionally classified in three major groups for clinical purposes, i.e., estrogen-receptor-positive (ER + ), HER2-positive (HER2 + ) and triple-negative (TNBC).…”
Section: Introductionmentioning
confidence: 99%